Brexit and foreign investment in the UK. (25th October 2018) - Driffield, Nigel; Karoglou, Michail
Summary: We explore the likely effect of Brexit on inward foreign direct investment (FDI) through its possible effect on the benchmark variables that characterize the macroeconomy. For this we propose the use of a Markov regime switching structural vector auto‐regression to distinguish between the volatile and stable states of the economy and account, among other effects, for the contemporaneous effects that the frequency of FDI innately generates. Our findings suggest that, if Brexit triggers a sterling depreciation in the current economic climate, this will fuel a prolonged negative effect on FDI. FDI flows may be positively affected (at most) by a sterling depreciation after Brexit only if this event drives the UK economy to a period of highly volatile growth, inflation, interest and exchange rates: a scenario that is rather unlikely. And, even then, the sterling depreciation benefits would last for only a short period of time.